Study of the composition of titanium oxide films deposited by reactive magnetron sputtering - Aubakirova, D.; Yerdybaeva, N.; Pichugin, V. (Recent Contributions to Physics, 2020)
The structure and properties of titanium oxide films deposited by reactive magnetron sputtering are studied. The results of the study of thin films using IR and Raman spectra show that the presence of a two-phase TiO2 structure and the formation of an N-O bond when nitrogen is introduced without the formation of titanium nitride (TiN), and may also indirectly indicate the presence of nitrogen oxide compounds in the film. It was found that the structure, element and phase composition of coatings depend on the value of the oxygen / nitrogen ratio in the composition of the reactive gas, as well as on the value of the negative displacement on the substrate. An increase in the proportion of nitrogen leads to a decrease in the spray rate. The obtained materials have the structure of anatase and rutile. The x-ray photoelectron spectroscopy method shows the presence of nitrogen (N) in The TiO2 lattice. In samples doped with nitrogen, a band appears in the Raman scattering spectra at 1048 cm-1 associated with the presence of nitrogen in TiO2. The elemental composition was also studied using an optical emission spectrometer of a glow discharge. Analysis of molecular bonding in the coatings was carried out using Fourier transform infrared spectroscopy. To measure Raman micro-spectra, a device developed at Fraunhofer IKTS-MD was used, consisting of a unit containing an inverted ZEISS optical microscope, Axiovert, and an iHR550 spectrometer with a cooled detector (Horiba, Jobin Yvon Inc.), A laser with a wavelength of 632.8 nm was used to excite the oscillations. Optical characteristics of coatings were studied on the spectral ellipsometric complex "Эллипс-1891 САГ" at a fixed angle of analysis of 70° in the range of wavelengths λ = 250-1000 nm.